EU COMMON VALUES: DEFINITION, STATUS AND CHALLENGES - Limantė, Agnė (Teisė, 2016)
The article analyses the concept and content of the key EU values as well as raises questions on Europe’s crisis of values. The paper is structured in three parts. The first part provides a detailed analysis of legal-philosophical foundations of values focusing on values in the context of EU as an international organisation. The second part introduces the reader to the key EU values embedded in Article 2 of the Treaty of the European Union as well as their normative content. It claims that belonging to the core of the EU’s legal-political system, Article 2 values represent a constitutional compass allowing the EU to stay the course. At the same, their enforcement relies solemnly on a special political procedure established by Article 7 TEU. The third part of the article is dedicated to present day challenges. The author claims that the EU is experiencing a crisis of values which is of new type and hard to overcome.